Autonomia da criança na aquisição da língua inglesa: um confronto entre as perspectivas de Vygotsky e psicanalítica. - Costa, Maria Eduarda Oliveira (2020)
The development of autonomy since childhood when learning a foreign language is a current topic and places the student as responsible for his own learning. Therefore, we have an individual, who will learn a foreign language in a classroom by interacting with other students and the teacher. This research has as main objective to investigate how the autonomy in foreign language acquisition can be thought within the perspectives of Vygotsky and the psychoanalysis of Freud and Lacan, putting these two points of view in confrontation. With regard to the acquisition of the mother tongue and the acquisition of a foreign language, we explore the proposals of Cláudia Lemos and Christine Revuz, respectively, both affected by psychoanalysis. To this end, a bibliographic study was developed, addressing the concepts of autonomy, subject, language, language, and interaction in the two theoretical perspectives, investigating how the teaching and learning of a foreign language can be found in the literature on autonomy in foreign language acquisition. In addition, foreign language teaching and learning was explored with a focus on student autonomy, describing the autonomous classroom, bringing the example of Leni Dam and emphasizing the importance of the mother tongue in foreign language learning. Finally, it was pointed out that there is a need for more studies on autonomy focusing on the student's peculiarities and on the way each one exercises control over their own learning, taking into account issues raised by the notion of the unconscious, more specifically by the subject’s body. In this respect, the present research brought indications that both perspectives approached bring important contributions, also pointing to the need for autonomy to be discussed through the psychoanalytic view, from authors who study foreign language acquisition along this research line. Finally, a teaching proposal that considers the dimension of desire, that is, of the unconscious, is still necessary.